Characteristics of air/water slug flow in an intermediate diameter pipe - Azzopardi, Barry J.; Do, H.K.; Azzi, A.; Hernandez Perez, V. (Elsevier, 2015)
Experiments have been carried out in a 67 mm diameter pipe with air and deionised water in which gas superficial velocities between 0.04 and 0.55 m/s were studied. A capacitance technique, employing electrodes mounted on either side of the outside of the acrylic resin pipe, has been used to provide time varying cross-sectionally averaged void fraction. Probability Density Functions of these data has permitted characterisation of the slug flow. Pressure drop measurements were made using differential pressure transducer. The mean void fraction, the void fraction in the slug region, the slug velocity and the dimensionless length of liquid slug all increase with the superficial gas velocity. On the other hand increasing the superficial gas velocity was shown to decrease the fractional slug length, the frequency and the film thickness around the Taylor bubble as well as the pressure gradient. A new version of the drift flux equation for bubble rise velocity is proposed and found to perform well against the present data and that from the literature.